Exploring Student Challenges in Learning Writing Descriptive Text : A Case Study Vocational School in Bekasi - Trastiawan, Rizky Ardianto; Wigati, Fikri Asih; Srisudarso, Mansyur (FKIP - Universitas Riau, 2025)
Writing is a fundamental language skill that plays a crucial role in academic and professional success. Descriptive writing, in particular, requires students to vividly portray ideas, experiences, or concepts using words. The purpose of this study is to provide educators and policy makers with valuable insights into targeted interventions to help students overcome barriers and achieve proficiency with writing descriptive. The use of a purposive sampling method ensures targeted selection of participants, taking into account factors such as program specialization. This is achieved by ensuring comprehensive representation of the student population, through a strategic selection of participants who will offer a variety of insights. n conclusion, The teacher uses the